INDUCTION OF ANTICANCER RESISTANCE IN MICE TREATED WITH LECTIN OF BACTERIAL ORIGIN - О. А. Танасієнко; М. П. Рудик; Г. П. Тітова; Г. П. Потебня (Mìkrobìologìâ ì Bìotehnologìâ. Мікробіологія і біотехнологія, 2010)
The preventive antitumor effect of cytotoxic lectin isolated from culture me- from culture medium Васillus subtilis B-7025 on the models of experimental tumours sarcoma-37, Ehrlich carcinoma and metastatic Lewis lung carcinoma was firstly shown. The injection of lectin to intact mice leads to stimulation of anticancer resistance to transplanted tumour cells, tumour growth inhibition and increasing of animal survival. Presurgical injection of lectin to Lewis lung carcinoma bearing mice was found to result in the substantial antimetastatic effect in surgical treated mice. Our results prove that cytotoxic lectin has mediate activating influence on antitumour immunity of animals.